A single-center retrospective study comparing safety and efficacy of endoscopic biliary stenting only vs. EBS plus nasobiliary drain for obstructive jaundice - Liu, Huan; Shi, Chuanke; Yan, Zhideng; Luo, Ming (Frontiers in Medicine, 2022)
Purpose Biliary drainage is an important modality for extrahepatic obstructive jaundice both in patients with palliative and resectable. Currently, endoscopic biliary drainage is preferred in clinical practice, including endoscopic nasobiliary drainage (ENBD) and endoscopic biliary stenting (EBS), both of which have their own advantages and disadvantages. The purpose of our study was to compare the safety and efficacy of endoscopic biliary stenting (EBS) only vs. EBS plus nasobiliary drain for obstructive jaundice. Methods We consecutively reviewed patients with endoscopic biliary drainage in our institution from November 2014 to March 2021. Combined (ENBD plus stent) and single approach (EBS only) were defined as combined approach and single modality, respectively, and all eligible patients were divided into a combined approach group and a single modality group. We compared combined vs. single modality approaches to investigate whether there were statistical differences in liver chemistries, postoperative adverse events, and stent patency time. Results In 271 patients, a total of 356 times endoscopic biliary drainages were performed. All eligible patients were divided into the combined approach group (n = 74) and the single modality group (n = 271). The combined approach was associated with a lower incidence of postoperative cholangitis and bleeding and greater improvement in liver chemistries, although it was not statistically significant. However, it was superior to the single modality group in terms of hospital stay (12.7 ± 5.2 vs. 14.5 ± 7.9 days, p = 0.020 < 0.05) and stent patency time (8.1 ± 3.9 vs. 4.3±2.7 months, p = 0.001 < 0.05). Conclusion Endoscopic combined (ENBD plus stent) drainage is a more advantageous biliary drainage method that is characterized by more adequate biliary drainage, a lower incidence of postoperative adverse events, and longer effective biliary drainage time.